Description Of Knowledge And Attitudes Of Grade 11 Female Adolescents About Personal Hygiene During Menstruationat St. Petrus Private Senior High School Medan In 2025 - Risda Mariana Manik; Bernadetha Br Barus; R. Oktaviance; Merlina Sinabariba (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2026)
Maintaining personal hygiene during menstruation is a crucial aspect of reproductive health, especially for adolescent girls. Lack of proper knowledge and attitude towards menstrual hygiene can lead to various health issues, including reproductive tract infections. This study aims to describe the knowledge and attitudes of 11th-grade female students regarding personal hygiene during menstruation. This descriptive research involved 57 respondents selected through purposive sampling. A questionnaire is used as the research instrument. The results revealed that 61.4% of respondents had good knowledge, 33.3% had moderate knowledge, and 5.26% had poor knowledge. Regarding attitudes, 70% of the respondents demonstrated positive attitudes, while 30% showed negative attitudes. It can be concluded that the majority of female students at the school have a good understanding and positive attitudes about menstrual hygiene. It is recommended that schools and health institutions continue to provide education to increase awareness and hygienic behavior during menstruation